2020
DOI: 10.3390/pr8111485
|View full text |Cite
|
Sign up to set email alerts
|

Optimising Brewery-Wastewater-Supported Acid Mine Drainage Treatment vis-à-vis Response Surface Methodology and Artificial Neural Network

Abstract: This study investigated the use of brewing wastewater (BW) as the primary carbon source in the Postgate medium for the optimisation of sulphate reduction in acid mine drainage (AMD). The results showed that the sulphate-reducing bacteria (SRB) consortium was able to utilise BW for sulphate reduction. The response surface methodology (RSM)/Box–Behnken design optimum conditions found for sulphate reduction were a pH of 6.99, COD/SO42− of 2.87, and BW concentration of 200.24 mg/L with predicted sulphate reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…ANN is a smart modeling technique that imitates the biological processing power of the human brain. It is capable of handling the simulation and modeling of very complex non‐linear systems 33 . Once a neural network has been successfully trained using the experimental dataset, it can be used to predict the results of a new set of input data by identifying the trained datasets.…”
Section: Introductionmentioning
confidence: 99%
“…ANN is a smart modeling technique that imitates the biological processing power of the human brain. It is capable of handling the simulation and modeling of very complex non‐linear systems 33 . Once a neural network has been successfully trained using the experimental dataset, it can be used to predict the results of a new set of input data by identifying the trained datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the preference for ANN above other optimization techniques like one‐variable‐at‐a‐time (OVAT) and response surface methodology (RSM), due to its inherent ability to predict complex and non‐linear relationships among the chosen process variables in optimization studies (Sewsynker‐Sukai et al, 2017). ANNs can adapt and simulate non‐linear and complicated interactions, which is crucial since many of the correlations between inputs and outputs, in reality, are non‐linear and multidimensional (Akinpelu et al, 2020). It can infer unobserved correlations after learning from the original inputs and their correlations, thereby allowing the model to generalize and predict the new dataset.…”
Section: Introductionmentioning
confidence: 99%
“…ANNs can adapt and simulate non-linear and complicated interactions, which is crucial since many of the correlations between inputs and outputs, in reality, are non-linear and multidimensional (Akinpelu et al, 2020). It can infer unobserved correlations after learning from the original inputs and their correlations, thereby allowing the model to generalize and predict the new dataset.…”
Section: Introductionmentioning
confidence: 99%